Pengaruh Penambahan Minyak Kelapa, Minyak Biji Bunga Matahari, dan Minyak Kelapa Sawit terhadap Penurunan Produksi Metan di dalam Rumen secara in Vitro (The Effect of Addition Coconut Oil, Sunflower Seed Oil, and Palm Olein on Reducing Ruminal Methane Pro - Puput Diah Sitoresmi; Lies Mira Yusiati; Hari Hartadi (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
This experiment was conducted to determine the effect of vegetable oil, such as coconut oil, sunflower seed oil, and palm olein on methane production, number of protozoa, microbial protein concentration, ammonia (NH3) concentration and carboxymethyl cellulase (CMC-ase) activity in the vitro fermentation of king grass and rice bran by rumen microbial. The experiment consisted of two treatments (i.e.) the effect of coconut oil, sunflower seed oil, and palm olein and level of addition of vegetable oil i.e. 0%, 2.5%, 5.0%, and 7.5%. The fermentation was done using Hohenheim gas test (HGT) metode and incubated at 39°C for 72 hours with three replicates. At the end of the fermentation, methane concentration, number of protozoa, microbial protein concentration, NH3 concentration, CMC-ase activity, and pH were observed. Data obtained were analyzed using analysis of variance and the design using factorial (3x4). The deferences of mean values were analyzed by Duncan’s new multiple range test (DMRT). The result showed that the number of protozoa decreased (P<0.05) as much as 9.8%, 20.85%, and 23.95%, followed by methane supression (P<0.01) much as 11.11%, 15.79%, and 18.51% with oil addition at level 2.5%, 5.0%, and 7.5% compared to control, but no effect on microbial protein concentration, ammonia (NH3) concentration and carboxymethyl cellulase (CMC-ase) activity. It can be concluded that coconut oil had the highest affect on methane production by inhibition ofprotozoa growth and addition oil up to 5.0% reduced methane production as much as 15.80%.(Key words : Coconut oil, Sunflower seed oil, Palm olein, Methane production, Protozoa count, In vitro fermentation)